Pendidikan Agama Islam Multikultural (dalam Perspektif Filsafat Pendidikan Islam dan Barat) - Sundari, Sundari; Haris, Abd; Mansur, Rosichin (LPPM Institut Pendidikan Nusantara Global, 2024)
The concept of multicultural education from the perspective of Islamic educational philosophy. The diversity that exists in this country can cause conflict due to differences of opinion between ethnicities, cultures, religions and so on, if it is not based on tolerance between one another. Multicultural education is an educational process that develops all human potential with various cultures, ethnicities and religions within it. The concept of multicultural education is expected to be able to minimize conflicts in society that occur due to differences in viewpoints, attitudes, cultures and so on. In Islam, Islamic educational philosophy is a science that examines various problems related to education, such as humans as subjects and objects of education, curriculum, methods, environment, teachers, and so on based on Islamic teachings which are based on the Koran and Al-Qur'an. Hadith. The Qur'an discusses a lot about the concept of multicultural education, such as the concept of getting to know and respect various cultures, races and religions, including Surah Al Hujurat verse 13 and Surah Yunus verse 99. Muslim philosopher M. Naquib Al Attas also gave his opinion regarding the multicultural concept, namely that individuals and society are not separated in the brotherhood of humanity, not only from a review of the historical social contract that has occurred, but also from a review of the primordial bonds that have existed between all humans created by God.